Developing the Quality Function Deployment Method by Integrating Kano Model and Sensory Profile Analysis into the House of Quality Matrix - Fauza, Gusti; Wimaryana, Viska Wandhira; Prasetyo, Hari; Ariviani, Setyaningrum; Muhammad, Dimas Rahadian Aji; Affandi, Dian Rachmawanti (Teknotan: Jurnal Industri Teknologi Pertanian, 2025)
This study aims to enhance the effectiveness of the Quality Function Deployment (QFD) method for food product development by integrating the Kano model and sensory profile analysis using Quantitative Descriptive Analysis (QDA) into the House of Quality (HOQ) matrix. The Kano model was applied to identify and categorize customer expectations, while QDA was used to characterize the sensory attributes of four steamed brownie samples—one of which was the target for improvement. Twelve quality attributes were identified, comprising both intrinsic (taste, aroma, texture, appearance) and extrinsic (packaging, labeling, branding, distribution) factors. Kano analysis revealed that two attributes were classified as Attractive, eight as One-dimensional, and two as Indifferent. Sensory profiling showed key differences between the developed product and a superior competitor. HOQ analysis indicated that improvements in formulation (composition of ingredients) and packaging design were critical for increasing consumer satisfaction. Unlike conventional QFD, which primarily translates customer requirements into technical specifications, the proposed integrative approach explicitly distinguishes attributes based on their impact on satisfaction (via Kano) and links them to measurable sensory characteristics (via QDA). This combination provides clearer prioritization and more actionable insights for product developers. Therefore, this study offers a structured and consumer-focused strategy that strengthens QFD’s applicability in the food industry by improving both accuracy and relevance in decision-making.